2021
DOI: 10.3390/molecules26247629
|View full text |Cite
|
Sign up to set email alerts
|

Carpachromene Ameliorates Insulin Resistance in HepG2 Cells via Modulating IR/IRS1/PI3k/Akt/GSK3/FoxO1 Pathway

Abstract: Insulin resistance contributes to several disorders including type 2 diabetes and cardiovascular diseases. Carpachromene is a natural active compound that inhibits α-glucosidase enzyme. The aim of the present study is to investigate the potential activity of carpachromene on glucose consumption, metabolism and insulin signalling in a HepG2 cells insulin resistant model. A HepG2 insulin resistant cell model (HepG2/IRM) was established. Cell viability assay of HepG2/IRM cells was performed after carpachromene/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 48 publications
(72 reference statements)
0
28
0
Order By: Relevance
“…The current focus on herbal products inspires scientists to investigate natural agents in many disorders [36][37][38][39]. Many studies have shown that natural components can play an essential role in preventing human diseases [40][41][42][43]. Among them, vincamine has been reported to shield human corneal epithelial cells (HCECs) from lipopolysaccharides (LPS)induced injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The current focus on herbal products inspires scientists to investigate natural agents in many disorders [36][37][38][39]. Many studies have shown that natural components can play an essential role in preventing human diseases [40][41][42][43]. Among them, vincamine has been reported to shield human corneal epithelial cells (HCECs) from lipopolysaccharides (LPS)induced injuries.…”
Section: Discussionmentioning
confidence: 99%
“…To further explain the mechanism of action of this new FAG, we investigated the expression of the EGFR protein before and after treatment on LPS- stimulated RAW 264.7 cells. EGFR has been studied extensively for developing anticancer agents [ 22 , 37 , 38 , 39 , 40 ]. Recently, several studies indicated that EGFR has a pathological role in non-neoplastic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, NSAIDs applications are limited by some side effects such as bronchospasm, thrombosis, gastrointestinal bleeding, and renal failure [ 17 ]. Accordingly, extensive studies are underway to identify and develop natural products that can be used as antioxidant and anti-inflammatory agents [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that more than 60% of current anticancer drugs come from natural sources [ 7 , 8 , 9 , 10 ]. In other pathophysiological conditions, such as cardiovascular diseases, diabetes mellitus, and multiple sclerosis, natural products have contributed clearly to the therapeutic protocols [ 11 , 12 , 13 , 14 ]. Some of the recently highlighted natural products are cytokinins (CKs), which have different pharmacological and medicinal actions.…”
Section: Cytokinins Occurrence Structure and Identificationmentioning
confidence: 99%